2007
DOI: 10.1590/s0100-879x2006005000108
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor properties of blackseed (Nigella sativa L.) extracts

Abstract: The objective of the present study was to evaluate the in vitro and in vivo anti-cancer effect of Nigella sativa L. seed extracts. The essential oil (IC 50 = 0.6%, v/v) and ethyl acetate (IC 50 = 0.75%) extracts were more cytotoxic against the P815 cell line than the butanol extract (IC 50 = 2%). Similar results were obtained with the Vero cell line. Although all extracts had a comparable cytotoxic effect against the ICO1 cell line, with IC 50 values ranging from 0.2 to 0.26% (v/v), tests on the BSR cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(103 citation statements)
references
References 15 publications
(17 reference statements)
4
86
0
7
Order By: Relevance
“…The results showed that both NSE and NSO of N sativa decreased the cell viability of A-549 cells in a concentration-dependent manner. Our results are well in ordinance with the previous studies showing in vitro anticancer activity of N sativa against the various cell lines (Ivankovic1et al, 2006;Bourgou et al, 2010;Raval et al, 2010), and in in vivo setup (Salomi and Panikkar, 1989;Mbarek et al, 2007). An in vitro study showed the significant cytotoxic activity (p<0.01) against L929 fibroblast cells in a concentration dependent manner (Ivankovic et al, 2006).The various studies also showed that extract of N sativa plant exhibits the inhibition of cancerous cell growth against HL-60 and U-937 cell lines (Raval et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that both NSE and NSO of N sativa decreased the cell viability of A-549 cells in a concentration-dependent manner. Our results are well in ordinance with the previous studies showing in vitro anticancer activity of N sativa against the various cell lines (Ivankovic1et al, 2006;Bourgou et al, 2010;Raval et al, 2010), and in in vivo setup (Salomi and Panikkar, 1989;Mbarek et al, 2007). An in vitro study showed the significant cytotoxic activity (p<0.01) against L929 fibroblast cells in a concentration dependent manner (Ivankovic et al, 2006).The various studies also showed that extract of N sativa plant exhibits the inhibition of cancerous cell growth against HL-60 and U-937 cell lines (Raval et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The seed extracts from N sativa have also been found active against DLD-1 colon carcinoma and Staphylococcus aureus and Escherichia coli bacterial strains (Bourgou et al, 2010). The administrations of the essential oil into the tumor site have also been shown to inhibit liver metastasis development and improved the survival of mouse/mice (Salomi and Panikkar, 1989;Mbarek et al, 2007). The active principles in NSO have been found to exert antineoplastic effects both in vitro and in vivo using various models of carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological actions of the seeds of Nigella sativa or its constituents that have been reported include protection against nephrotoxicity and hepatotoxicity induced by either disease or chemicals [6][7][8][9][10][11][12][13][14]. The seeds/oil have anti-inflammatory [15], analgesic [4], antipyretic [16], spasmolytic [17], bronchodialator [17], antihistaminic [18], antihypertensive [19], antitumor [20], antioxidant [18], antineoplastic [9,21,22], antifertility [23], antibacterial [24], antifungal [25], antiprotozoal [26], anthelmintic [27] and insecticidal [28] activities. Treatment of rats with the seed extract for up to 12 weeks has been reported to induce changes in the hemogram that include an increase in both the packed cell volume and hemoglobin [29] and a decrease in plasma concentrations of cholesterol, triglycerides and glucose [30].…”
Section: Review and Discussionmentioning
confidence: 99%
“…In fact, sustained delivery of thymoquinone (derived from N. sativa) is almost as effective in causing apoptosis of colon cancer cells as sustained delivery of 5-fluorouracil [3] . Similarly, hepatic metastasis from tumors such as mastocytomas is markedly decreased following administration of N. sativa [4] . N. sativa, when used in combination with Hemidesmus indicus and Smilax glabra, also seems to decrease hepatic carcinogenesis secondary to exposure to agents such as diethylnitrosamine [5] .…”
Section: To the Editormentioning
confidence: 98%